FORMS OF PROVIDING LOANS TO SMALL BUSINESSES - Gaybullayev , Sarvar (Scientific practical conference, 2025)
this article serves small business and business entities show, with the expansion of production in small business entities their technical repair, material and technical support, storage of products, range of services such as operation and sales, communication and communication, consulting and information information about types is presented.